"The Nature of Managerial Work - The Case for Unobtrusive Measures Revisited" - A Reply. - Wolf, Frank M. (The Accounting Review, 1981)
Abstract In this article, the author responds to comments of the analyst Paul A. Ryder on his research paper "The Nature of Managerial Work." The author says that Ryder raises a number of general methodological issues about organizational research and the critical incident methodology which have been well documented in the literature. Issues raised are ones regularly revisited by organizational theorists and are, in general, issues which have not been unambiguously resolved. Measures which intrude may elicit atypical roles and responses, and, to the extent that they do, these measures are said to be reactive. Research methods may be obtrusive without necessarily being reactive, and conversely research methods may be reactive while not being particularly obtrusive. For the purpose of describing the nature of managerial work in large organizations, a number of research methodologies have been used. Suggestions that stereotyped perceptions from different organizational levels is a product of the methodology applied, is a critique which provides some cause for concern.